Leveraging Module Conditional Release to Support Evidence-Based Practices - Sarah Johnson (Journal of Teaching and Learning with Technology)
Large enrollment, asynchronous online courses pose many teaching and learning challenges. Instructors want to use evidence-based practices like building connections with students, providing personalized support, giving quick feedback on formative assessments, and encouraging student engagement and self-regulation within the course. Yet, large asynchronous online classrooms can make those important evidence-based practices difficult. This Quick-Hit provides a detailed overview of module conditional release, a learning management system tool that can support instructors in achieving these evidence-based practices in large online courses. The application of conditional release and supporting tools and strategies will be discussed alongside a description of how instructors can leverage this technological support to better connect with students, provide personalized support, produce feedback opportunities on formative assessment and encourage student engagement and self-regulation, all at scale.